(untitled) (Research, Society and Development, 2021)
Composites are conjugated combinations of two or more materials, which comprehend a matrix and one or more types of reinforcements. Its applicability spans several industrial sectors, mainly in the aerospace and transport sectors. Its use has grown in recent years, but its usefulness depends on several factors such as the way of manufacture, type of resin, applied reinforcement and the environment to be exposed. In addition, this type of material suffers degradation in its useful life, so it is necessary to know its behavior, as they are potential waste generators, bringing concerns to the environment. From this, the work had, as main objective, the manufacture of a composite material that was exposed to two different environments, sea water and sand, for a period designated from moisture saturation. The specimens were submitted to density, humidity and calcination tests. After moisture saturation, the specimens were superficially evaluated using scanning electron microscopy (SEM), making it possible to visualize the wear suffered during the exposure of the material. Then, it was identified that in both environments there was a superficial wear, with more intensity, mainly, in the exposed to the sea water. Therefore, it was possible to conclude that this type of composite, once exposed to these conditions, highlights the need to add a new layer of material in order to protect its structure, increasing its useful life and mitigating the generation of waste in the environment.